PENGARUH PEMBERIAN BAHAN ORGANIK TERHADAP DAYA SIMPAN BENIH KEDELAI {Glycine max (L.) Merr.} - Sudirman Umar (BERITA BIOLOGI, 2012)
Fertilization with organic and inorganic fertilizers increase the availability of nutrients in the soil and improve soil physical and chemical properties, The nutrient must fulfill crop requirement regarding to its effect to seed quality. The object of experiment was to study the effect of a combination organic fertilizer and inorganic fertilizer to resilience of soybean {Glycine max (L.) Merr.} seed var. Anjasmoro. Storage of seeds, were conducted in the Post Harvest Laboratory of Balai Penelitian Pertanian Lahan Rawa-Balittra (Indonesian Swampland Agriculture Institute), Banjarbaru from October 2009 until April 2010. The experiment was designed in completely randomized with 4 replications. Seed water content, seed germination, vigor index, electrical conductivity and seedling development were observed. The results showed that during storage, water content of seed increased 3-4% and limit the water content of seeds was still able to be maintained at <13%. Organic matter and NPK fertilizer declined vigor and germination of seed. Vigor is still above 70% and germination as high as >77%; As lower as seed germination generate as higher as electrical conductivity and lower the seedling dry weight.